Щодо виникнення трудового права Європейського союзу - Гаєвая, Олександра Валентинівна (НТУ "ХПІ", 2017)
У статті досліджується інтеграція в загальносвітову систему правового регулювання праці, яка передає іншим країнам власний нормотворчий і практичний досвід в трудовій сфері. Відстежується звільнення трудового права від застарілих і неефективних конструкцій, запозичення в міру необхідності різноманітних концепцій в теорії і практиці різних регіонів світу. Демонструється адаптація їх до внутрішньодержавних особливостей і потреб на сучасному етапі. Зазначається, що завдяки Європейському трудовому праву створено збірник модельних правових норм.

In the article the integration into the general world system of the legal regulation of labor which conveys to other countries its own normative and practical experience in the labor sphere has been investigated. The deliverance of the labor law from the constructions becoming obsolete and inefficient, borrowing when the necessity arises of numerous concepts in the theory and practice of the world different regions has been tracked. The adaptation of them to the peculiarities and needs within the state at the present day stage has been demonstrated. It is noted that, thanks to the European Labor Law, the collection of model legal norms, the creative application of which is a prerequisite for the development and improvement of any national system of international labor law has been created and it is made an attempt to bring to conformity the general civilized requirements. The formation of the European Union labor law under the influence of conceptual constructions and practices inherent to the national legal systems of member states and international law has been shown. Their transformation and use, taking into account the goals, tasks and the necessity of the most effective solution of the problems related to their jurisdiction, have been analyzed. The law of the European Union, being integrated by character, introduces the uniform standards of conduct for citizens and organizations in many spheres of their lives, thereby laying the legal foundations for creation of "as much as possible the closest union of the peoples of Europe". In the norms of the given legal system, the principles of the single internal market and the legal regime of the single currency (euro), the status of the institutions (the European Parliament, the Council of the European Union, etc.) and legal entities, a single (Schengen) Visa and other persons have been enshrined.
The emergence of the labor law of the European Union
Keywords: інтеграція економічна; стандарти трудові; право міжнародне; уніфікація; переміщення ресурсів; співробітництво міждержавне; права людини; economic integration; labor standards; unification; relocation of resources; interstate cooperation; human rights